Sistematic Evaluative Research about an Innovation Project in Secondary Education to Dealing with Student Diverstiy. "Multilevel Cooperative Classroom" - Gerardo Echeita; Carlos Jury (Universidad Autónoma de Madrid, 2018)
The article approaches the possibilities that the metaphor like instrument offers to include/understand and to explain the educative and organizational phenomena, and as strategy of analysis of the reality. The metaphor can get to become or to be the own thought that is developed or to be a resource with which it is possible to construct knowledge. As it will be reflected in the article, the metaphors are something more than a simple appeared resource. From the diversity of examples that can be found in Literature, one will go to track the origins of the metaphor in the educative speech and organizational, to arrive at the aspects it nails that they are had to consider when the methaphor expression like instrument from analysis of the organizational and educative reality of the schools is taken: discursive context, use given to the metaphor and micropolitical context.